Technologies for public services - Macaya, Javiera Fernanda Medina; Ribeiro, Manuella Maia; Lima, Camila dos Reis; Dhaou, Soumaya Ben; Isagah, Tupokigwe; Magalhães, Larissa (Comitê Gestor da Internet no Brasil, 2025)
32 p.